“A quality of heart, of presence, and of really caring”: toward affirmative intersex health communication in Canada - Knoppers, Terese; Voutsinas, Angelica; Palmour, Nicole; Saulnier, Kaleb; Holmes, Morgan; Charron, Marilou; Gallois, Hortense; Jamali, Narges; Ordal, Leslie; Joly, Yann (Frontiers in Public Health, 2025)
IntroductionThis qualitative research study aimed to better understand and help improve the Canadian context for health communication with intersex adults by centering the voices of those directly involved and impacted.MethodsWe conducted 22 semi-structured interviews with intersex individuals (14) and healthcare practitioners (HCPs, 8) from diverse areas of care. Interviews were analyzed via template thematic analysis and filtered through a conceptual lens that brought together agency-based and social-ecological models of health communication.ResultsFindings produced three interlocking axes for change: HCP skills and approaches, structural access to care, and norms and discourses. Participant accounts depict a landscape for intersex health communication where practices are improving, but adverse experiences are still commonplace and intersex individuals cannot assume HCPs will be competent in intersex care. Rather, they utilize a variety of strategies and expend considerable efforts navigating structural gaps and barriers to access affirmative HCPs, who themselves often gained their expertise via individual initiative. Interviewees advocated for HCPs to get a baseline background in intersex care during their medical training, as well as skills in accessible health communication and person-centered and trauma-informed approaches. They also connected broader societal stigma and pathologization to harmful medical practices and called for naturalization and normalization of intersex variations.ConclusionThis study highlights the need for collaborative efforts across multiple sectors and by multiple stakeholders to drive meaningful change. Findings can help guide HCPs, medical educators, researchers, advocates, and policymakers towards accessible, affirmative, and agency-based care.